Manifestation of a plateau response in VO2 at maximal oxygen uptake is a function of the anaerobic work capacity - Gordon, D.; Baker, J.; Johnstone, J.; Barnes, R.; Scruton, A.; Merzbach, V. (19th Annual Congress of the European College of Sport Science (ECSS), Amsterdam, 2. - 5. July 2014, 2014)
Introduction: Variations in plateau incidence at VO2max are shown to be related to the size of the finite anaerobic capacity (AnC). However, the AnC only refers to substrate availability and does not reflect changes in intracellular metabolites associated with fatigue processes which are evident at VO2max. The anaerobic work capacity (AWC) (W`) derived from the power-time relationship in concert with critical power (CP) defines the interaction between anaerobic substrate metabolism and metabolite accumulation, potentially providing a more plausible explanation for variances in plateau response. Therefore, the purpose of this study was to evaluate the association between W` and the incidence of plateau at VO2max in a cohort of trained individuals. Method: Following University Institutional ethical approval, 15 males (age, 24.4 ± 5.19 yrs; height, 179.3 ± 6.7 cm; mass, 79.6 ± 12.9 kg; VO2max, 47.8 ± 6.9 ml/kg/min) volunteered to participate. Each participant reported to the laboratory on 5 separate occasions, visits 1 and 5 for the determination of VO2max, while for the remaining 3 visits, tests to exhaustion were completed for determination of CP and W`. All trials were completed on an electronically braked cycle ergometer at a constant cadence of 80-100 rpm with work-rate (VO2max) increasing by 0.42 W/s following a 60 s period at 100 W. Using a pre-calibrated metabolic cart, plateau responses were determined using the criteria of ÄVO2 <1.5 ml/kg/min over the final two consecutive 30 s sampling periods. For CP trials, intensity was assigned on Pmax from VO2max 1 with individual trials completed at ~120, 100 and 95% Pmax. CP and W` were derived using a linear P -1/t model and solving the equation P=AWC.(1/t) + CP. Results: Seven participants exhibited a plateau response (RE), ÄVO2 ml/kg/min (0.73 ± 0.53) compared to non-responders (NRE) (n= 8) of 2.4 ± 0.4 ml/kg/min (P= 0.005). For RE a significant inverse correlation was observed between ÄVO2dif ml/kg/min (difference between criterion and actual response) and W` (P= 0.030) but not for NRE (p> 0.05). Additionally there were no differences for VO2max, CP or Pm x for RE and NRE (p> 0.05). CP was however significantly correlated to VO2max for RE (P= 0.064) and NRE (P= 0.008). Discussion: These data suggest that the manifestation of the plateau at VO2max as expressed as a function of the AWC, representing the balance between the finite anaerobic capacity, accumulation of the fatigue induced metabolites and O2 bound to haemoglobin and myoglobin. The findings lend support to the classical interpretation for a cardiac limitation to VO2max and offer further insight into the issues surrounding plateau attainment.